1993
DOI: 10.1001/archsurg.1993.01420220022003
|View full text |Cite
|
Sign up to set email alerts
|

Gasless Laparoscopy and Conventional Instruments

Abstract: Comparable exposure was achieved in this cohort of patients with gasless laparoscopy. The use of conventional surgical instruments provides an advantage with this technique. Further improvements in abdominal wall lift systems and modification of existing surgical instruments may expand the role of gasless laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(22 citation statements)
references
References 10 publications
(1 reference statement)
0
22
0
Order By: Relevance
“…By eliminating the use of many disposable laparoscopic instruments, hospitals can reduce the costs of treating patients without affecting the standards of patient care. The use of gasless laparoscopy and conventional instruments has also been shown to be safe and cost effective [14]. This would not only lower the variable costs incurred by each patient but also lower the relative proportion of intraoperative costs associated with diagnostic or therapeutic laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…By eliminating the use of many disposable laparoscopic instruments, hospitals can reduce the costs of treating patients without affecting the standards of patient care. The use of gasless laparoscopy and conventional instruments has also been shown to be safe and cost effective [14]. This would not only lower the variable costs incurred by each patient but also lower the relative proportion of intraoperative costs associated with diagnostic or therapeutic laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigators have reported a variety of abdominal wall lifting devices [1,6,8,10,11,13], yet abdominal wall lifting methods have not gained general acceptance. The reasons are as follows: (1) narrow visual field and small operating space due to the straight side wall of the abdominal cavity [14]; (2) the requirement for additional abdominal wounds and potential for increased postoperative pain; and (3) the time required for preoperative assembly of the retractor system.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgical instruments could be easily used when needed [13]. The assembly was inexpensive and manufactured locally.…”
Section: Discussionmentioning
confidence: 99%